IMGT/StatClonotype for Pairwise Evaluation and Visualization of NGS IG and TR IMGT Clonotype (AA) Diversity or Expression from IMGT/HighV-QUEST - Aouinti, Safa; Giudicelli, Véronique; Duroux, Patrice; Malouche, Dhafer; Kossida, Sofia; Lefranc, Marie-Paule (Frontiers in Immunology, 2016)
There is a huge need for standardized analysis and statistical procedures in order to compare the complex immune repertoires of antigen receptors immunoglobulins (IG) and T cell receptors (TR) obtained by next generation sequencing (NGS). NGS technologies generate millions of nucleotide sequences and have led to the development of new tools. The IMGT/HighV-QUEST, available since 2010, is the first global web portal for the analysis of IG and TR high throughput sequences. IMGT/HighV-QUEST provides standardized outputs for the characterization of the ‘IMGT clonotype (AA)’ (AA for amino acids) and their comparison in up to one million sequences. Standardized statistical procedures for ‘IMGT clonotype (AA)’ diversity or expression comparisons have recently been described, however no tool was yet available. IMGT/StatClonotype, a new IMGT® tool, evaluates and visualizes statistical significance of pairwise comparisons of IMGT clonotype (AA) diversity or expression, per V (variable), D (diversity) and J (joining) gene of a given IG or TR group, from NGS IMGT/HighV-QUEST statistical output. IMGT/StatClonotype tool is incorporated in the R package ‘IMGTStatClonotype’, with a user-friendly interface. IMGT/StatClonotype is downloadable at IMGT® (http://www.imgt.org/StatClonotype/) for users to evaluate pairwise comparison of IG and TR NGS statistical output from IMGT/HighV-QUEST and to visualize, on their web brower, the statistical significance of IMGT clonotype (AA) diversity or expression, per gene, the comparative analysis of CDR-IMGT and the V-D-J associations, in immunoprofiles from normal or pathological immune responses.